Report on the use of medicinal plants among pregnant women treated at the Centro de Salud Viña Alta, La Molina. Lima, Peru - Echevarría-Merino, H (2021)
This research aimed to find out the frequency and ways of using medicinal plants by pregnant women treated at the Centro de Salud Viña Alta, located in La Molina district. Twenty-one (21) pregnant women voluntarily participated in the study, where they were administered an expert-validated survey regarding the use of medicinal plants. The results showed that 86 % of the pregnant women used medicinal plants and 67 % did not ask their doctor before using them. The most frequent way of using the medicinal plants was by oral intake as herbal teas. The most widely used medicinal plants were chamomile, parsley, eucalyptus, boldo, aloe, mint and rue, some of which produced a teratogenic effect, uterine stimulant action, abortifacient effect, among others. It is necessary to know the actual quantity and most frequent way of using medicinal plants by pregnant women to classify these products as for its safety level and promote the rational use of traditional medicine to contribute to public health.